Brain longevity [soundrecording] - Singh Khalsa, Dharma (Time Warner Audio Books, 1997)
Presents the use of modern complementary medicine from Eastern and Western traditions including nutritional therapy, stress management, exercise therapy and pharmacology, all designed to reduce the effects of "normal" brain aging. The program presented is designed to control a specific adrenal hormone, control, which has been shown to be toxic to the brain at certain levels and to become present in excessive levels as we age.